(untitled) (Revista Innova Educación, 2024)
En the current era, the acquisition and dissemination of knowledge occur swiftly, generating the need to update the way it is obtained and, above all, how information is managed. For this reason, it is of utmost importance that students, especially university students, cultivate the ability to handle information efficiently. The aim of this study was to determine the influence exerted by the application of flipped learning on the development of proper management of academic information in trainee teachers at the National University "San Luis Gonzaga," Ica-Peru. The adopted approach was quantitative with a pre-experimental design. The sample consists of 27 intentionally and conveniently selected students. An evaluation rubric with five assessment criteria and 10 items was applied, validated through Cronbach’s alpha, and obtained high reliability (0.852). For the hypothesis test, the obtained p-value (0.0000) supports the significance of the difference in favor of post-test results compared to pre-test results. When implementing flipped learning, the overall classroom averages regarding the variable of academic information management increased significantly. It was concluded that the use of flipped learning positively and significantly influences the development of the dependent variable and that its use is highly beneficial in fostering various skills in students, such as managing the information they require.